2021
DOI: 10.3389/fgene.2021.731391
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Mendelian Randomization Analysis of the Association Between Serum Calcium Levels and the Risk of Alzheimer’s Disease

Abstract: It has been a long time that the relationship between serum calcium levels and Alzheimer’s disease (AD) remains unclear. Until recently, observational studies have evaluated the association between serum calcium levels and the risk of AD, however, reported inconsistent findings. Meanwhile, a Mendelian randomization (MR) study had been conducted to test the causal association between serum calcium levels and AD risk, however, only selected 6 serum calcium SNPs as the instrumental variables. Hence, these finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…Calcium has been found to have a protective role in AD development, while oversupplementation of calcium has also been shown to increase the risk of AD. Extracellular accumulation of amyloid plaques and intracellular neurofibrillary tangles in the brain is present in AD, and calcium dysregulation has been shown to induce synaptic deficits and promote the accumulation of the plaques and neurofibrillary tangles [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium has been found to have a protective role in AD development, while oversupplementation of calcium has also been shown to increase the risk of AD. Extracellular accumulation of amyloid plaques and intracellular neurofibrillary tangles in the brain is present in AD, and calcium dysregulation has been shown to induce synaptic deficits and promote the accumulation of the plaques and neurofibrillary tangles [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…He and others selected 8 genome-wide significant and independent serum calcium genetic variants as the instrumental variables, and found that per 1 standard deviation increase in serum calcium level (about 0.5 mg/dL) contribute to a reduced risk of AD using IVW (OR = 0.57) ( He et al, 2020 ). Shi and others further conducted an updated MR analysis in both discovery stage and replication stage ( Shi et al, 2021 ). In the discovery stage, 14 independent but not genome-wide significant serum calcium genetic variants were selected as the instrumental variables ( Shi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shi and others further conducted an updated MR analysis in both discovery stage and replication stage ( Shi et al, 2021 ). In the discovery stage, 14 independent but not genome-wide significant serum calcium genetic variants were selected as the instrumental variables ( Shi et al, 2021 ). In the replication stage, 166 genome-wide significant and independent serum calcium genetic variants were selected as the instrumental variables ( Shi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca homeostasis disruption promotes Aβ and tau pathology [ 239 ]. However, human studies have produced contradictory results, with both decreased [ 240 , 241 ] and increased Ca [ 186 , 242 ] being risk factors. In recent MR studies, higher Ca levels were shown to reduce the risk of AD [ 241 , 243 ], or no association between Ca levels and AD risk has been observed [ 218 , 220 ] ( Table 3 ).…”
Section: Essential Metals In Alzheimer’s Diseasementioning
confidence: 99%